Non-linear association between metabolic score for insulin resistance and diabetes mellitus in normal-weight middle-aged and older Chinese adults: a multicenter retrospective cohort study - Cai, Hualang; Cai, Zhimao; Cai, Qingxian (Frontiers in Nutrition, 2026)
BackgroundAlthough the link between the metabolic score for insulin resistance (METS-IR) and diabetes mellitus (DM) is well-established in general populations, it remains underexplored in normal-weight middle-aged and old adults—an often-overlooked group in metabolic research. Therefore, this study investigated the association between METS-IR and diabetes in this specific population.MethodsA retrospective cohort study was conducted using data from the Rich Healthcare Group database, including 23,692 normal-weight (body mass index: 18.5–23.9 kg/m2) Chinese adults aged ≥45 years. Cox proportional hazards models were applied with adjustments for demographic, clinical, and biochemical confounders. Non-linearity was examined using smooth curve fitting and threshold effect analysis.ResultsHigher METS-IR values were significantly correlated with greater diabetes risk during follow-up. In the model 3, each 1-unit rise in METS-IR corresponded to a 12% increase in diabetes risk (HR: 1.12, 95% CI: 1.10, 1.14). The analysis revealed a non-linear association, with a critical inflection point at a METS-IR of 37.24. Below this threshold, risk rose more sharply (HR: 1.18, 95% CI: 1.14, 1.21 per unit), whereas above the threshold, the association was attenuated (HR: 0.96, 95% CI: 0.89, 1.04). Subgroup analyses showed largely consistent findings across strata.ConclusionsAmong normal-weight middle-aged and older Chinese adults, METS-IR exhibits a positive, non-linear relationship with DM risk. Maintaining a lower METS-IR may help prevent the development of DM.